Overview of Mink Immunity and Resistance to Pseudomonas aeruginosa - Jiangsong Bai; Xiao Wang; Zihui Zhang; Pengjing Lian; Jian Qiao (Veterinary Medicine International)
Pseudomonas aeruginosa is one of the most host-susceptible pathogenic bacteria to cause acute and chronic infections in humans and animals. Notably, its infection can especially cause fatal pathogenic infectious pneumonia in minks. Many previous mink studies have investigated the pathology, pathogenesis, serology, antimicrobial resistance, virulence gene, vaccination, and related diseases of P. aeruginosa. However, the relationship of P. aeruginosa infections with mink immunity and resistance is relatively less studied that needs more elaborations. Therefore, we here provide a comprehensive review about mink immunity and resistance to P. aeruginosa infections and the pathogenesis of mink hemorrhagic pneumonia in four major aspects. They include characterization, infection, immunity, and resistance of P. aeruginosa, and their implication and perspective, which aim to contribute the useful and valuable information to further related research and clinical treatment of P. aeruginosa and to avoid the potential fatal hemorrhagic pneumonia spreading.